Method for preparing CoTi oxide alloy electrocatalyst using cotton fiber
The use of CoTi oxide alloy electrocatalysts prepared from cotton fibers addresses the high cost and low activity of traditional metal-air battery cathodes by providing a cost-effective, stable, and efficient alternative with enhanced catalytic performance for oxygen reduction and evolution reactions.
Patent Information
- Application Number
- CN202211231658.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-08
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-10-08
AI Technical Summary
Existing metal-air battery cathodes face challenges with high cost, low reserves, and insufficient catalytic activity due to the use of precious metal catalysts like Ru/Ir-based and Pt-based materials.
A method is developed to prepare CoTi oxide alloy electrocatalysts using cotton fibers, replacing precious metals with non-precious metals, involving impregnation, high-temperature calcination, and doping with C and N to enhance the catalyst's surface structure and electrochemical performance.
The CoTi oxide alloy electrocatalyst achieves performance comparable to or exceeding that of noble metal catalysts, with wide availability, low cost, and improved stability, demonstrating excellent bifunctional electrochemical performance for oxygen reduction and evolution reactions.
Smart Images

Figure CN115369438B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing an air cathode of a metal battery. Background Art
[0002] Environmental issues and energy crises have driven the rapid development of efficient and clean energy conversion and storage applications. Metal-air batteries have attracted widespread attention due to their high safety, low cost and zero carbon emissions. Among all energy storage and conversion applications, metal-air batteries have attracted much attention due to their high theoretical specific energy and low cost. However, oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) are considered to be the key factors to solve metal-air batteries because they have multiple proton-coupled electron transfer steps and high-energy intermediates. Therefore, studying efficient and stable OER and ORR performance has become a very critical part. The commercially available OER and ORR catalysts on the market are precious metal iridium-based metal oxides and platinum-based catalysts, which are not suitable for widespread application due to their high cost and natural scarcity. Therefore, the use of transition metals abundant in the earth to prepare efficient bifunctional catalysts has become a research hotspot.
[0003] Metal-air batteries are a special type of fuel cell that uses metal as fuel to generate electricity through a redox reaction with oxygen in the air. There are a variety of raw materials available for making metal-air batteries. The metal-air batteries that have made research progress include aluminum-air batteries, magnesium-air batteries, zinc-air batteries, and lithium-air batteries. The metal catalysts used in the cathode of metal-air batteries are Ru / Ir-based and Pt-based catalysts, which have the disadvantages of low reserves, high cost, and insufficient bifunctional catalytic activity. Summary of the invention
[0004] The present invention aims to solve the technical problems of high cost, low reserves and low catalytic activity of existing metal catalysts used in metal-air battery cathodes, and provide a method for preparing CoTi oxide alloy electrocatalysts using cotton fibers. The catalyst of the present invention replaces part or all of the precious metals with non-precious metal catalysts, so that its performance is close to or exceeds the level of precious metal catalysts; in terms of cost, it is low-priced, widely available, and has sufficient reserves; and is superior to precious metal catalysts in terms of stability and other properties.
[0005] The method for preparing CoTi oxide alloy electrocatalyst using cotton fiber of the present invention is carried out according to the following steps:
[0006] 1. Preparation of impregnation solution: according to the molar ratio of Co, Ti and N atoms being (3-6):1:(1-3), cobalt nitrate hexahydrate, tetrabutyl titanate and acetamide are weighed respectively, and added into N,N-dimethylformamide, and stirred at room temperature until completely dissolved to obtain an impregnation solution;
[0007] 2. Preparing impregnated cotton fiber: impregnating the cotton fiber as a C source into the impregnation solution obtained in step 1, at a temperature of 20° C. to 35° C. and a relative humidity of 20% to 35% for 12 to 24 hours, and drying to obtain a precursor;
[0008] 3. Preparation of CoTi oxide alloy electrocatalyst: Place the precursor in a tubular furnace, heat it to 700-900°C in a N2 atmosphere, and sinter it at a constant temperature for 1-2 hours to obtain a CoTi oxide alloy electrocatalyst, denoted by CoTiCN.
[0009] Furthermore, the total mass concentration of cobalt nitrate hexahydrate and acetamide of tetrabutyl titanate in the impregnation solution in step 1 is 10% to 30%.
[0010] Furthermore, the drying in step 2 is performed by placing the product in an oven at 80° C. for 12 to 24 hours.
[0011] Furthermore, the heating rate of step 3 is 4-5°C / min.
[0012] The application of the CoTi oxide alloy electrocatalyst prepared by the above method is to use the catalyst to prepare the cathode of a metal-air battery.
[0013] Furthermore, the method for preparing a metal-air battery cathode using a CoTi oxide alloy electrocatalyst is carried out according to the following steps:
[0014] 1. First, grind the glassy carbon electrode on the suede with aluminum oxide powder with particle sizes of 1.0, 0.3, and 0.05 microns in sequence until the electrode surface is smooth and flat without scratches, then clean the electrode surface with deionized water, and then clean the electrode surface with ultrasound for 10 seconds, and finally blow dry for standby use;
[0015] 2. Weigh 3 mg of CoTi oxide alloy electrocatalyst powder, add it to 1 mL of 0.5% Nafion aqueous solution, and disperse it by ultrasonic for 30 minutes to obtain a catalyst suspension with a concentration of 3 mg / mL;
[0016] 3. Add the catalyst suspension dropwise onto the polished glassy carbon electrode and let it stand at room temperature for 1 hour. After the catalyst dries and forms a film, the metal-air battery cathode is obtained.
[0017] The present invention uses cotton fiber as a template, soaks the cotton fiber in a solution containing metal and doping elements, uses non-metallic elements C and N to dope and modify CoTi oxide, combines high-temperature calcination to change the surface structure of the catalyst and produce pyridine nitrogen and graphite nitrogen, and makes the surface metal and non-metallic elements show good dispersibility, increases the specific surface area, generates a mesoporous structure, and improves the electrochemical performance of the CoTi oxide alloy electrocatalyst.
[0018] The present invention uses a CoTi oxide alloy electrocatalyst metal air battery cathode, which has excellent bifunctional electrochemical performance and excellent stability to oxygen reduction reaction.
[0019] The CoTi oxide alloy electrocatalyst of the present invention reaches or exceeds the performance of noble metal iridium-based metal oxides and platinum-based catalysts, and has a wide source of raw materials and low price, and can be used in the field of metal-air batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is a scanning electron microscope photograph of CoTiCN prepared in Example 1;
[0021] Figure 2 is a scanning electron microscope photograph of CoTi prepared in Comparative Example 1;
[0022] Figure 3 This is a scanning electron microscope photo of CoTiC prepared in Comparative Example 1;
[0023] Figure 4 is a scanning electron microscope photograph of CoTiCS prepared in Comparative Example 2;
[0024] Figure 5 is a scanning electron microscope photograph of CoTiCNS prepared in Comparative Example 3;
[0025] Figure 6 are XRD spectra of CoTiCN, CoTi, CoTiC, CoTiCS and CoTiCNS prepared in Example 1 and the comparative example;
[0026] Figure 7 is a BET curve diagram of CoTiCN, CoTi, CoTiC, CoTiCS and CoTiCNS prepared in Example 1 and the comparative example;
[0027] Figure 8 is a pore size distribution curve diagram of CoTiCN, CoTi, CoTiC, CoTiCS and CoTiCNS prepared in Example 1 and the comparative example;
[0028] Fig. 9 It is the full XPS spectra of CoTiCN, CoTi, CoTiC, CoTiCS and CoTiCNS prepared in Example 1 and the comparative example;
[0029] Fig.10 High-resolution N1s spectra of CoTiCN and CoTiCNS prepared in Example 1 and Comparative Example
[0030] Fig.11is the OERLSV curve of catalytic glassy carbon electrodes prepared using CoTiCN, CoTi, CoTiC, CoTiCS and CoTiCNS;
[0031] Fig.12 is the OERLSV Tafel slope plot of catalytic glassy carbon electrodes prepared using CoTiCN, CoTi, CoTiC, CoTiCS and CoTiCNS;
[0032] Fig.13 It is the impedance spectra of catalytic glassy carbon electrodes prepared using CoTiCN, CoTi, CoTiC, CoTiCS and CoTiCNS;
[0033] Fig.14 It is the ORRLSV curve of catalytic glassy carbon electrodes prepared using CoTiCN, CoTi, CoTiC, CoTiCS and CoTiCNS;
[0034] Fig.15 is the ORRLSV Phil slope diagram of catalytic glassy carbon electrodes prepared using CoTiCN, CoTi, CoTiC, CoTiCS and CoTiCNS;
[0035] Fig.16 is a graph showing the number of transferred electrons and hydrogen peroxide yield of catalytic glassy carbon electrodes prepared using CoTiCN, CoTi, CoTiC, CoTiCS and CoTiCNS;
[0036] Fig.17 It is the differential capacitance test graph of catalytic glassy carbon electrodes prepared by CoTiCN, CoTi, CoTiC, CoTiCS and CoTiCNS;
[0037] Fig.18 This is a stability curve of the CoTiCN oxide alloy electrocatalyst prepared in Example 1 before and after cycling. DETAILED DESCRIPTION
[0038] The beneficial effects of the present invention are verified by the following examples.
[0039] Example 1: The method for preparing CoTi oxide alloy electrocatalyst using cotton fiber in this example is carried out according to the following steps:
[0040] 1. Preparation of impregnation solution: Cobalt nitrate hexahydrate and acetamide of tetrabutyl titanate are weighed respectively according to the molar ratio of Co, Ti and N atoms being 4:1:3, and added into N,N-dimethylformamide, and stirred at room temperature until completely dissolved to obtain an impregnation solution; wherein the total mass percentage concentration of cobalt nitrate hexahydrate, tetrabutyl titanate and acetamide in the impregnation solution is 10%;
[0041] 2. Preparation of impregnated cotton fiber: impregnating the cotton fiber into the impregnation solution obtained in step 1 for 12 hours at a temperature of 30° C. and a relative humidity of 30%, taking it out and drying it in an oven at 80° C. for 24 hours to obtain a precursor;
[0042] 3. Preparation of CoTi oxide alloy electrocatalyst: The precursor was placed in a tubular furnace, heated to 800°C at a rate of 5°C / min in a N2 atmosphere, and sintered at a constant temperature for 2h to obtain a CoTi oxide alloy electrocatalyst, denoted by CoTiCN.
[0043] Comparative Example 1: This embodiment is different from Embodiment 1 in that the composition of the impregnation liquid is different. The specific steps are as follows:
[0044] 1. Preparation of impregnation solution: Cobalt nitrate hexahydrate and tetrabutyl titanate are weighed respectively according to a molar ratio of Co to Ti of 4:1, and added into N,N-dimethylformamide, and stirred at room temperature until completely dissolved to obtain an impregnation solution; wherein the total mass percentage concentration of cobalt nitrate hexahydrate, tetrabutyl titanate and acetamide in the impregnation solution is 10%;
[0045] 2. Preparation of impregnated cotton fiber: impregnating the cotton fiber into the impregnation solution obtained in step 1 for 12 hours at a temperature of 30° C. and a relative humidity of 30%, taking it out and drying it in an oven at 80° C. for 24 hours, taking it out, and obtaining a precursor;
[0046] 3. Preparation of CoTi oxide alloy electrocatalyst:
[0047] The precursor was placed in a tube furnace, heated to 800°C at a rate of 5°C / min in a N2 atmosphere, and then sintered at a constant temperature for 2 hours to obtain a CoTi oxide alloy electrocatalyst, denoted by CoTiC.
[0048] The precursor was placed in a tubular furnace, heated to 800°C at a rate of 5°C / min in an O2 atmosphere, and then sintered at a constant temperature for 2 hours to obtain a CoTi oxide alloy electrocatalyst, denoted by CoTi.
[0049] Comparative Example 2: This embodiment is different from Embodiment 1 in that the composition of the impregnation liquid is different. The specific steps are as follows:
[0050] 1. Preparation of impregnation solution: Cobalt nitrate hexahydrate, tetrabutyl titanate and thiourea are weighed respectively according to the molar ratio of Co, Ti and S being 4:1:0.5, and added into N,N-dimethylformamide, and stirred at room temperature until completely dissolved to obtain an impregnation solution; wherein the total mass percentage concentration of cobalt nitrate hexahydrate, tetrabutyl titanate and thiourea in the impregnation solution is 10%;
[0051] 2. Preparation of impregnated cotton fiber: impregnating the cotton fiber into the impregnation solution obtained in step 1 for 12 hours at a temperature of 30° C. and a relative humidity of 30%, taking it out and drying it in an oven at 80° C. for 24 hours to obtain a precursor;
[0052] 3. The precursor was placed in a tubular furnace, heated to 800°C at a rate of 5°C / min in a N2 atmosphere, and then sintered at a constant temperature for 2 hours to obtain a CoTi oxide alloy electrocatalyst, denoted by CoTiCS.
[0053] Comparative Example 3: This embodiment is different from Embodiment 1 in that the composition of the impregnation liquid is different. The specific steps are as follows:
[0054] 1. Preparation of impregnation solution: Cobalt nitrate hexahydrate, tetrabutyl titanate, acetamide and thiourea are weighed respectively according to the molar ratio of Co, Ti, N and S being 4:1:3:0.5, and added into N,N-dimethylformamide, and stirred at room temperature until completely dissolved to obtain an impregnation solution; wherein the total mass percentage concentration of cobalt nitrate hexahydrate, tetrabutyl titanate, acetamide and thiourea in the impregnation solution is 10%;
[0055] 2. Preparation of impregnated cotton fiber: impregnating the cotton fiber into the impregnation solution obtained in step 1 for 12 hours at a temperature of 30° C. and a relative humidity of 30%, taking it out and drying it in an oven at 80° C. for 24 hours to obtain a precursor;
[0056] 3. Preparation of CoTi oxide alloy electrocatalyst:
[0057] The precursor was placed in a tubular furnace, heated to 800°C at a rate of 5°C / min in a N2 atmosphere, and then sintered at a constant temperature for 2h to obtain a CoTi oxide alloy electrocatalyst, which was recorded as CoTiCNS.
[0058] The CoTiCN, CoTi, CoTiC, CoTiCS and CoTiCNS prepared in Example 1 and the comparative example were tested by scanning electron microscopy. The scanning electron microscope photos of CoTiCN are as follows: Figure 1 As shown, the scanning electron microscope image of CoTi is Figure 2 As shown, the scanning electron microscope photo of CoTiC is as follows Figure 3 As shown in the SEM image of CoTiCS Figure 4 As shown in the SEM images of CoTiCNS Figure 5 As shown. Figures 1 to 5It can be seen that cotton fibers are soaked in a solution containing metals and doping elements, and then calcined at high temperature, so that the metals and doping elements are adsorbed on the surface of the cotton fibers. By observing the scanning electron microscope images, it can be found that due to the high-temperature calcination of CoTi in the air, the cotton fiber structure that is not resistant to high temperatures in the catalyst is oxidized, leaving only metals and their oxides, so the surface of the catalyst structure is broken. Among them, CoTiCN, CoTiC, CoTiCS and CoTiCNS all present the morphology of cotton fiber structures. When observing the surface of the structure, agglomeration occurs on the surface of CoTiCS and CoTiCNS. The metal and non-metal elements on the surface of the CoTiCN structure show good dispersion, and the particle dispersion is better than that of CoTi, CoTiC, CoTiCS and CoTiCNS catalysts. The surface roughness is relatively high. Such a structure effectively increases the contact area between the catalyst and the reactants and improves the electrochemical performance.
[0059] The CoTiCN, CoTi, CoTiC, CoTiCS and CoTiCNS prepared in Example 1 and the comparative example were subjected to XRD test, and the obtained XRD spectra were as follows: Figure 6 As shown, from Figure 6 It can be seen that metal elements, oxides and compounds appear in the samples. Among them, sharp CoCo2O4 and elemental Co phases appear in the CoTiCN sample. The metal oxides and metal elements are embedded in the cotton fiber carbon structure after high-temperature calcination in an inert gas environment, which is beneficial to improve the electrocatalytic performance.
[0060] The CoTiCN, CoTi, CoTiC, CoTiCS and CoTiCNS prepared in Example 1 and the comparative example were subjected to BET test, and the obtained BET curves are shown in the figure below. Figure 7 As shown, from Figure 7 It can be seen that in the N2 protected environment, CoTiCN, CoTiC, CoTiCS and CoTiCNS all present type IV nitrogen adsorption curves, indicating that CoTiCN, CoTiC, CoTiCS and CoTiCNS are all mesoporous structures.
[0061] The CoTiCN, CoTi, CoTiC, CoTiCS and CoTiCNS prepared in Example 1 and the comparative example were subjected to pore size distribution test. The pore size distribution curves obtained are as follows: Figure 8 The specific surface area and pore size data are shown in Table 1. Figure 8 As can be seen from Table 1, the sample structure is multi-level pores, mainly mesopores. Among them, CoTiCN has a high specific surface area and mesoporous structure, which is beneficial to improve the transmission rate of ions and electrons during the catalytic reaction and increase the diffusion channels of reactants, products and electrolytes during the reaction.
[0062] Table 1 Specific surface area and pore size test results of CoTiCN, CoTi, CoTiC, CoTiCS and CoTiCNS prepared in Example 1 and Comparative Example
[0063] sample <![CDATA[Specific surface area (m 2 g -1 )]]> Pore size (nm) CoTiCN 110.578 3.828 CoTi 10.147 1.69 CoTiC 65.116 3.833 CoTiCS 42.958 3.826 CoTiCNS 111.5 1.423
[0064] The CoTiCN, CoTi, CoTiC, CoTiCS and CoTiCNS prepared in Example 1 and the comparative example were subjected to XPS full spectrum testing. The obtained XPS spectra are as follows: Fig. 9 As shown, the full spectrum shows the presence of metal elements and non-metal elements used for modification in the sample.
[0065] The high-resolution N1s spectra of CoTiCN and CoTiCNS prepared in Example 1 and the comparative example are Fig.10 It can be seen that there are pyridinic nitrogen and graphitic nitrogen in CoTiCN and CoTiCNS, which are beneficial to improve the bifunctional electrocatalytic activity of OER and ORR, while nitrogen oxide and pyrrolic nitrogen have no obvious enhancement effect on the catalytic activity of OER and ORR. The content of pyridinic nitrogen and graphitic nitrogen in CoTiCN accounts for a larger proportion than that in CoTiCNS.
[0066] The CoTiCN, CoTi, CoTiC, CoTiCS and CoTiCNS prepared in Example 1 and the comparative example were used as catalysts to prepare electrodes respectively. The specific method is as follows: a glassy carbon electrode adopts a rotating ring disk electrode with a diameter of 4 mm. The glassy carbon electrode is first repeatedly polished in an eight-shaped or circular shape on suede with aluminum oxide powder with a particle size of 1.0, 0.3, and 0.05 microns in sequence until the surface of the electrode is smooth and flat without scratches. Then, the electrode surface was cleaned with deionized water, and then ultrasonically cleaned for 10 seconds, and finally dried with an ear bulb for standby use; 3 mg of catalyst powder was weighed and added to 1 mL of 0.5% Nafion aqueous solution, and ultrasonically dispersed for 30 minutes to obtain a catalyst suspension with a concentration of 3 mg / mL; 10 μL of the catalyst suspension was drawn with a microinjector and dropped onto the polished glassy carbon electrode, and allowed to stand at room temperature for 1 hour. After the catalyst dried and formed a film, a metal-air battery cathode, i.e., a catalytic glassy carbon electrode, was obtained. The surface area of the glassy carbon electrode was 0.1256 cm 2 .
[0067] At room temperature, a catalytic glassy carbon electrode was used as the working electrode, an Ag / AgCl electrode was used as the reference electrode, a platinum wire was used as the auxiliary electrode, and the electrolyte used was 0.1 M KOH solution. The following electrochemical tests were performed using a standard three-electrode system.
[0068] Electrochemical tests were performed using an electrochemical workstation and a rotating disk electrode device. During the OER test, the electrode rotation speed was 1600 rpm, the scanning speed was 5 mV / s, and the scanning potential range was 0.2 to 1.0 V. The obtained OER LSV curve is shown in Fig.11 As shown, from Fig.11 It can be seen that at 10 mA cm -2 At high current density, the performance of CoTiCN is better than that of other samples.
[0069] The Tafel slopes of the catalytic glassy carbon electrodes using CoTiCN, CoTi, CoTiC, CoTiCS and CoTiCNS as catalysts are shown in Fig.12 As shown in Figure 2, the Tafel slope shows the effect of non-metallic element doping on the kinetic performance of the catalyst reaction. Among them, CoTiCN has a relatively low Tafel slope, and the results prove that the N-doped CoTi oxide alloy catalyst has excellent OER catalytic reaction kinetic performance.
[0070] The impedance spectra of catalytic glassy carbon electrodes with CoTiCN, CoTi, CoTiC, CoTiCS and CoTiCNS as catalysts were tested in the frequency range of 0.1-10000 Hz and amplitude of 5 mV. Fig.13 As shown, from Fig.13 It can be seen that CoTiCN has the smallest resistance, indicating that CoTiCN has higher charge transfer efficiency and the best OER reaction kinetics.
[0071] The ORR LSV curves of CoTiCN, CoTi, CoTiC, CoTiCS and CoTiCNS as catalytic glassy carbon electrodes were tested. The ORR LSV curves are shown in the figure. Fig.14 As shown, from Fig.14 It can be seen that CoTiCN has the highest half-wave potential and the largest limiting current density, indicating that the CoTiCN catalyst has high catalytic activity.
[0072] The effect of non-metallic element doping on the kinetic performance of the catalyst reaction was studied by calculating the Tafel slope, such as Fig.15 The CoTiCN shown has a relatively low Tafel slope, and the results demonstrate that the N-doped CoTi oxide alloy catalyst has excellent ORR catalytic reaction kinetics.
[0073] In order to further study the reaction path of the ORR catalytic process, the electron transfer number (n) and hydrogen peroxide yield of the catalyst were calculated by the rotating ring disk electrode (RRDE) method. The obtained transfer electron number and hydrogen peroxide yield curve are shown in Fig.16The results show that compared with other catalysts, the lowest hydrogen peroxide yield of CoTiCN catalyst at 0.3-0.5V is less than 1.5% and the higher number of transferred electrons is greater than 3.9, indicating that the ORR reaction process of CoTiCN catalyst follows a four-electron transfer pathway. The lower hydrogen peroxide yield is beneficial to prevent the corrosion of hydrogen peroxide on the carbon support and the battery during the reaction.
[0074] Double-layer differential capacitance (C) of the CoTiCN oxide alloy electrocatalyst prepared in Example 1 dl ) value to evaluate the electrochemically active specific surface area of the catalyst. Fig.17 The potential scanning range of the CV test is 1.25-1.35 V, and the scanning speed range is 20-100 mV s -1 . The non-Faraday current in this range can be used to study the adsorption and desorption behavior of the electrode surface and determine the true active specific surface area of the electrode. Among them, the electrochemically active area of CoTiCN is much larger than that of other catalysts. The results show that the electrochemically active specific surface area of N-doped CoTi oxide alloy electrocatalyst increases significantly, which is mainly due to the fact that co-doping can produce more phase interfaces and defect structures, thereby significantly increasing the number of active sites.
[0075] The cycle curve of the CoTiCN oxide alloy electrocatalyst prepared in Example 1 is as follows: Fig.18 As shown, from Fig.18 It can be seen that the electrochemical performance of CoTiCN did not show a significant decrease after 1000 CV cycles.
[0076] From the control experiments of catalysts doped with different non-metallic elements, it can be seen that CoTiCN has higher catalytic activity than CoTi, CoTiC, CoTiCS and CoTiCNS. This is because the morphology, composition and structure of CoTiCN are different from those of other materials. The CoTiCN catalyst has highly dispersed active sites and obtains excellent OER / ORR bifunctional catalytic activity.
Claims
1. A method for preparing a CoTi oxide alloy electrocatalyst using cotton fiber, characterized in that The method proceeds as follows:
1. Preparation of impregnation solution: according to the molar ratio of Co, Ti and N atoms being (3-6):1:(1-3), cobalt nitrate hexahydrate, tetrabutyl titanate and acetamide are weighed respectively, and added into N,N-dimethylformamide, and stirred at room temperature until completely dissolved to obtain an impregnation solution; 2. Preparing impregnated cotton fiber: impregnating the cotton fiber as a C source into the impregnation solution obtained in step 1, at a temperature of 20° C. to 35° C. and a relative humidity of 20% to 35% for 12 to 24 hours, and drying to obtain a precursor; 3. Preparation of CoTi oxide alloy electrocatalyst: Place the precursor in a tubular furnace, heat it to 700-900°C in a N2 atmosphere, and sinter it at a constant temperature for 1-2 hours to obtain a CoTi oxide alloy electrocatalyst, denoted by CoTiCN.
2. The method for preparing CoTi oxide alloy electrocatalyst using cotton fiber according to claim 1, characterized in that The total mass concentration of cobalt nitrate hexahydrate and acetamide of tetrabutyl titanate in the impregnation solution in step 1 is 10% to 30%.
3. The method for preparing CoTi oxide alloy electrocatalyst using cotton fiber according to claim 1 or 2, characterized in that: The drying described in step 2 is to place the mixture in an oven at 80° C. for 12 to 24 hours.
4. The method for preparing CoTi oxide alloy electrocatalyst using cotton fiber according to claim 1 or 2, characterized in that The heating rate in step 3 is 4-5°C / min.
5. Application of the CoTi oxide alloy electrocatalyst prepared by the method of claim 1, characterized in that The application is to use the catalyst to prepare the cathode of metal-air batteries.
6. Use of the CoTi oxide alloy electrocatalyst according to claim 5, characterized in that The method for preparing a metal-air battery cathode using a CoTi oxide alloy electrocatalyst is carried out in the following steps:
1. First, grind the glassy carbon electrode on the suede with aluminum oxide powder with particle sizes of 1.0, 0.3, and 0.05 microns in sequence until the electrode surface is smooth and flat without scratches, then clean the electrode surface with deionized water, and then clean the electrode surface with ultrasound for 10 seconds, and finally blow dry for standby use; 2. Weigh 3 mg of CoTi oxide alloy electrocatalyst powder, add it to 1 mL of Nafion aqueous solution with a mass percentage concentration of 0.5%, and ultrasonically disperse it for 30 minutes to obtain a catalyst suspension with a concentration of 3 mg / mL; 3. Add the catalyst suspension dropwise onto the polished glassy carbon electrode and let it stand at room temperature for 1 hour. After the catalyst dries and forms a film, the metal-air battery cathode is obtained.
Citation Information
Patent Citations
Bifunctional oxygen catalyst and preparation method thereof
CN111883787A
